Fenomena Kapitalisme Tersembunyi dalam Kehidupan Suku Baduy Luar - Jason Fernando; Ezra Yora Turnip; Kezia Feradris; Jeremy Bryce Lim; Abharina Nasution (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to explain that the anomalies created by globalization are driving changes that the public in general is not aware of, where the Baduy people, especially the Outer Baduy, are starting to violate the traditions they hold. Globalization has encouraged hidden capitalism which has succeeded in breaking into the realm of daily life and activities carried out by the Outer Baduy people because the area they live in has been used as a tourist attraction and this has become an opportunity for capitalists to achieve maximum profits; by building market chains (mini markets, accommodation and other public facilities), distributing their products to the Outer Baduy community for sale, and forcing the community to integrate with modern culture such as using smartphones, modern equipment and consuming food. light. Hegemony is the reason this hidden power dynamic of capitalism persists in the lives of the Outer Baduy people, by instilling consumer values and promoting certain products as symbols of status and modernity. This research uses a qualitative analysis method which is based on objective observation; and also uses secondary data obtained through library data collection techniques. This research concludes the need to fight against the hegemony of capitalism through awareness and solidarity from traditional leaders together with the Outer Baduy community in maintaining their traditions and values so that they remain sustainable in the future.